2011
DOI: 10.4081/rt.2011.e35
|View full text |Cite
|
Sign up to set email alerts
|

Radiotherapy in the treatment of gastrointestinal stromal tumor

Abstract: Gastrointestinal stromal tumors (GISTs) are uncommon mesenchymal tumors of the gastrointestinal tract. Up to one-third of GISTs are malignant with a high rate of metastasis. Surgical resection is the mainstay of care for patients with resectable disease. Imatinib mesylate, a selective tyrosine kinase inhibitor, is the current standard of care for GISTs that cannot be completely resected or in cases of metastatic GIST. Although often overlooked, radiation therapy is a viable option for select patients with GIST… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 8 publications
0
20
0
Order By: Relevance
“…The logic behind this approach is that if resistance arises clonally, in conjunction with close CT or PET/CT observation, isolated areas of growth may be identified and deleted prior to more widespread dissemination of the resistant disease. 75-77 Within the Phase I study of crizotinib, thirty-seven patients continued to receive crizotinib for >2 weeks post-progression at the investigator’s discretion, 11 for more than 6 months from the time of their initial protocol-defined progression. 43 Although no formal details are available, in many cases this continuation likely occurred after areas of localized progression in both the body and/or CNS were treated with radiotherapy.…”
Section: Coming Challenges: Ascribing Value To Local Therapy For ‘Olimentioning
confidence: 99%
“…The logic behind this approach is that if resistance arises clonally, in conjunction with close CT or PET/CT observation, isolated areas of growth may be identified and deleted prior to more widespread dissemination of the resistant disease. 75-77 Within the Phase I study of crizotinib, thirty-seven patients continued to receive crizotinib for >2 weeks post-progression at the investigator’s discretion, 11 for more than 6 months from the time of their initial protocol-defined progression. 43 Although no formal details are available, in many cases this continuation likely occurred after areas of localized progression in both the body and/or CNS were treated with radiotherapy.…”
Section: Coming Challenges: Ascribing Value To Local Therapy For ‘Olimentioning
confidence: 99%
“…Of note, patients treated with a dose per fraction >5 Gy (n=8) had a radiographic response rate of 63%, suggesting that GISTs are more sensitive to a higher radiation dose. Knowlton et al reported 20 years of durable local control in a 37-year-old man treated in the pre-imatinib era with debulking surgery and 36 Gy for an unresectable, non-metastatic GIST 47. Similarly, local control was reported in six of nine patients treated with 45–60 Gy of radiation for incompletely resected disease in the pre-imatinib era 48.…”
Section: The Rationale For Radiation Therapy (Rt)mentioning
confidence: 96%
“…Thus, radiotherapy has been historically administered in GIST patients only with a palliative/antalgic aim and mainly for bone metastases. However, a few experiences show that selected patients could benefit from radiotherapy in specific sites, thus obtaining not only high rates of palliation for symptomatic tumors in a cohort of advanced-stage, heavily pretreated patients, but also initial tumor shrinkage and subsequent durable disease stabilization [71][72][73][74][75]. In this sense, radiotherapy integrated with systemic therapy could provide an important benefit in selected patients with progressive or metastatic disease.…”
Section: Tki-radiotherapymentioning
confidence: 99%